2014
DOI: 10.9775/kvfd.2013.9988
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Saccharomyces cerevisiae and Spirulina platensis on Growth Performances and Biochemical Parameters in Rabbits

Abstract: A feeding trial was conducted to evaluate the effect of live yeast culture Saccharomyces cerevisiae (SC) and Spirulina platensis (SP) on the growth performance and serum biochemical parameters in rabbits. Forty, male New Zealand white rabbits, aged 5-6 weeks, were studied in 4 groups. The groups; I. Control (basal diet), II. SC (added 3 g/kg diet), III. SP (added 5% of the diet), IV. SC and SP (added 3 g/kg SC and 5% SP of the diet), respectively. The experiment lasted for 90 days. Blood samples were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…Further, decrease in cholesterol content of eggs of laying hens and broilers diets containing yeasts was reported by Yalçın et al [20] and Yıldız et al [21] . Seyidoğlu and Galip [22] and Seyidoğlu et al [23] were conducted to evaluate the effect of Saccharomyces cerevisiae on the serum biochemical parameters in rabbits. The diets with the yeast reduced serum HDL cholesterol and triglycerides on the 90 th feeding day.…”
Section: Discussionmentioning
confidence: 99%
“…Further, decrease in cholesterol content of eggs of laying hens and broilers diets containing yeasts was reported by Yalçın et al [20] and Yıldız et al [21] . Seyidoğlu and Galip [22] and Seyidoğlu et al [23] were conducted to evaluate the effect of Saccharomyces cerevisiae on the serum biochemical parameters in rabbits. The diets with the yeast reduced serum HDL cholesterol and triglycerides on the 90 th feeding day.…”
Section: Discussionmentioning
confidence: 99%
“…The results were in compliance with the finding of Abdel-Khalek et al (2012) who studied the effect of two levels (1 and 1.5% EM) of microorganisms supplementation (EM1) for growing New Zealand White rabbit (7 weeks of age) and found an increase in concentration of total protein, albumin, globulin and glucose in the group fed 1.5% EM1treatment. Seyidoglu and Galip (2014) reported a non-significant increase for blood glucose for those received S. cerevisiae (3 g/kg diet) from control. Moreover, Sarat Chandra et al (2015) reported that there was non-significant increase in blood glucose level for rabbits when fed with probiotics (Saccharomyces boulardi 50% and Pediococcus acidilacticii 50%, 109 CFU/g of feed) and enzymes (Kemzyme HF at 500 g/Ton of feed).…”
Section: Biochemical Parametersmentioning
confidence: 94%
“…On contrary, Dorra et al (2013) stated that use of dietary organic acids did not significantly influence growth performance, carcass traits or blood parameters of New Zealand White × California experimental rabbits, moreover Seyidoglu and Galip (2014) observed that final body weight and total weight gain was not affected significantly (P>0.05) for a period of 90 days when male New Zealand White rabbits (aged 5-6 weeks) raised on supplemented diet with live yeast culture. There was no significant difference between means (P > 0.05).…”
Section: Weekly Body Weight and Weight Gainmentioning
confidence: 95%
“…There are many different studies that point out the growth performance of S. platensis in animals [50][51][52][53][54][55][56][57]. For example, Moreira et al [50] studied the Wistar rat using S. platensis as an added nutrient at 8.8, 17.6, and 26.4% doses of forage.…”
Section: Effect Of S Platensis On the Growth Of Bacteria And Animalsmentioning
confidence: 99%
“…On the other hand, although some researchers found positive effects of S. platensis as a supplement with fish [52], some of them reported no significant changes in growth performances in fish [53,54]. Seyidoglu and Galip [51] tried to elucidate the effects of S. platensis on growth performance in rabbits. They indicated that there was a positive effect of supplementing S. platensis on growth performance due to dose, animals, and environmental changes.…”
Section: Effect Of S Platensis On the Growth Of Bacteria And Animalsmentioning
confidence: 99%